Managing Social Prejudication And Religious Ethnic Stereotypes Through Psychological And Global Education - Syafrianto Tambunan (IAIN Padangsidimpuan, 2020)
The series of conflicts that we see happening in Indonesia is inseparable from ethnic religion and culture, although there are factors such as structural inequality and system injustice. This factual reality might bring potential conflict, meaning that the latent danger of these factors can turn into a sensitive attitude. Some social analyzes assume that the potential for conflict becomes latent because the education system is unable to touch the psychological aspects of individual counseling and mental management in interacting with the community and its social environment. This study was categorized as literature research and field. describing or describing the social prejudices and ethnic stereotypes of religion that we see in Indonesia and based on the results of research journals/books that explain the stereotypes of ethnic religion. This paper will explain how to manage social prejudice and religious ethnic stereotypes through psychological and global education in the context of religious and cultural pluralism